Evaluation of two-group interfacial area transport equation model for vertical small diameter pipes against high-resolution experimental data. (27th April 2017) - Dave, Akshay J.; Manera, Annalisa; Beyer, Matthias; Lucas, Dirk; Bernard, Matthew
Abstract: Two-phase flow is ubiquitous in industrial, chemical and thermal plants alike. The current state-of-the-art system-code model for predicting fluid transport in two-phase flows is the two-fluid model. In the two-fluid transport model, the coupling of mass, momentum and energy transfer between phases is highly dependent on interfacial area transfer terms. Several research efforts in the past have been focused on the development of an interfacial area transport equation model (IATE) in order to eliminate the drawbacks of static regime flow maps currently used in best-estimate thermal-hydraulic system codes. The IATE attempts to model the dynamic evolution of the vapor/liquid interface by accounting for the different interaction mechanisms affecting gaseous phase transport. The further development and validation of IATE models has been hindered by the lack of adequate experimental data in regions beyond the bubbly flow regime. At the Helmoltz-Zentrum Dresden-Rossendorf (HZDR) experiments utilizing wire-mesh sensors have been performed over all flow regimes, establishing a database of high-resolution (in space and time) data. A 52.3 mm diameter pipe with a 16 by 16 wire-mesh sensor operating at 2.5 kHz is utilized in the air-water experimental database used in this work. There are a total of 37 tests (with varying superficial gas and liquid velocities, at approximately 0.25 MPa). Analysis of IATE performance in the bubbly flow and slug flow regimes is presented. The performance of the Fu-Ishii two-group IATE model is evaluated. In all regions, the interfacial area concentration for small bubbles is predicted well. The model performs poorly in high void fraction regimes, in which large irregularly shaped bubbles are present. The interaction mechanisms that support and deter performance of the IATE model are highlighted. A sensitivity analysis indicates modification of the group-2 wake entrainment coefficient may extend the validity of the Fu-Ishii model. An optimization study is presented to further explore improving IATE performance. It is concluded that the availability of accurate data at high void fractions from the HZDR facility provides a path to improve IATE performance.